Assessing the Foundations of Conscious Computing: A Bayesian Exercise - Horvitz, Eric (2001)
Questions have long been posed with about whether we might one day be able to create systems that experience subjective states similar to those experienced by people. The challenge of understanding and explaining conscious experience extends well beyond discussions among philosophers. Many people, including AI scientists pursuing principles of automated reasoning and decision making, and neurobiologists and psychologists with interests in nervous systems and cognition reflect about the nature of subjective states.